Peran Gereja Guna Mengurangi Kasus KDRT dalam Jemaat - Polyongkico, Polyongkico; Nelsen, Nelsen (Jurnal Kala Nea, 2022)
Domestic Violence (KDRT) can happen anywhere and to anyone, including the congregation. The research objectives to be achieved from this study are to describe the role of the church in congregational domestic violence victims and to describe the study of pastoral counseling for victims of domestic violence. The method used in this study is a descriptive method with a qualitative approach. In writing this research the author wants to explain the role of the church in the congregation to help victims of domestic violence, with several forms that the church does, namely: first: paying attention to victims and visiting victims in giving care in the sense of hearing complaints and strengthening and providing input that can help a victim (pastoral counseling). Second: providing assistance in the form of medical treatment and psychological (mental) treatment. So the role of the church is also to help victims of domestic violence that can happen to the congregation, and the church can build a Christian family based on belief in Jesus Christ.